2021
DOI: 10.1111/cen.14493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of serum immunoglobulin G4 in glucocorticoid therapy of Graves’ ophthalmopathy

Abstract: Objective Previous study suggested IgG4 levels were associated with the development of Graves’ ophthalmopathy (GO). The aims of the present study were to investigate the role of IgG4 levels in glucocorticoid (GC) treatment in GO patients. Design 69 GO patients were enrolled. Serum thyroid hormones, thyroid antibodies, IgG, IgG4, ophthalmological examinations and orbital MRI were performed. Furthermore, the clinical outcomes (a composite response endpoint including the clinical activity score (CAS), proptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…For instance, one study from 2021 revealed on 69 consecutive subjects with Graves’ ophthalmopathy that one third of them had an increased level of serum IgG4 while blood IgG4 correlated with the disease’s activity and severity. However, this sub-group had a statistically significant better response (and outcome) to glucocorticoid therapy than patients with normal serum IgG4 [ 86 ]. Another study from 2023 on 60 patients with active Graves’ disease revealed that high serum IgG4 levels (which were found in 25% of the subjects) might serve as a marker of activity [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study from 2021 revealed on 69 consecutive subjects with Graves’ ophthalmopathy that one third of them had an increased level of serum IgG4 while blood IgG4 correlated with the disease’s activity and severity. However, this sub-group had a statistically significant better response (and outcome) to glucocorticoid therapy than patients with normal serum IgG4 [ 86 ]. Another study from 2023 on 60 patients with active Graves’ disease revealed that high serum IgG4 levels (which were found in 25% of the subjects) might serve as a marker of activity [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-related thyroid diseases have been proposed as a distinct entity in the thyroid disease spectrum [ 32 ]. Our team previously found that this subgroup of GO patients with elevated serum IgG4 levels had a more severe form of GO but a better response to GC treatment than did those with normal IgG4 levels [ 19 ]. Other studies reported that RTX is an effective treatment for IgG4-related diseases, even without concomitant GC therapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methods for ophthalmic and biochemical examinations and MRI assessment were as described in our previous study [ 19 ], except that we analyzed the MRI features of the involved EOMs reported by the radiologist instead of the four recti [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because PC can obstruct the PD and lead to the occurrence of pancreatitis, it is not easy to judge the cause and effect of the two. Seeking efficient identification methods is the direction of clinical research (21,22). 85 patients who were diagnosed and treated at the dermatology clinic of XXX Hospital from October 10, 2016 to October 15, 2022 were included, with IgG4-related AIP patients in group A1 and PC patients in group A2, and MRI images were obtained.…”
Section: Discussionmentioning
confidence: 99%